RETRACTED: Cultural consumption as a parameter of the quality of life in a Russian megapolis - Babaeva Anastasia; Makarova Alexandra; Chougounova Tatiana; Chepurnova Natalya; Smetanina Tatiana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001